MAQASID DAN PERSONAL GROOMING Estetika, Hadits Mencukur Bulu Ketiak, dan Maslahah - Ali Akhbar Abaib Mas Rabbani Lubis; Abdul Rafik (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2020)
This study discusses the aesthetics of personal grooming in which contains recommendations for shaving underarm hair. This research is included in the study of literature commonly referred to as literature study, the object of this study is the hadith relating to personal grooming, especially the recommendation of shaving underarms assisted by the approach of maqasid al-shari'ah al-Syatibi. The result is that this personal grooming, related to hygiene and health, is in accordance with the concept of maqasid al-shari’ah in Islam, which is the aim of realizing benefit. Shaving armpit hair is agreed to Sunnah and favoured, pulling armpit hair has an impact on personal hygiene and health grooming in Islam emphasizes cleanliness and health,- the thing about the recommendation of shaving armpit is very basic and important for personal grooming.